Psoriasis and Seborrheic Keratoses: Insights from Biologic Therapy and Skin Imaging - Florin Ciprian Bujoreanu; Diana Sabina Radaschin; Mihail Alexandru Badea; Laura Bujoreanu Bezman; Carmen Pantiș; Carmen Tiutiuca; Liliana Baroiu; Elena Niculeț; Alina Pleșea Condratovici; Alin Laurențiu Tatu (Life)
Psoriasis is one of the most frequent immune-mediated chronic inflammatory cutaneous disease that exerts a considerable psychological impact, including low self-esteem, stigmatization, and depression. In recent years, biologic therapies have substantially transformed the therapeutic landscape for individuals with moderate-to-severe psoriasis, shifting treatment towards a more targeted and personalized approach. Seborrheic keratoses (SKs) are common benign skin lesions, and their association with psoriasis and biologic therapy remains poorly understood. Our retrospective study evaluated a small cohort of patients with moderate-to-severe psoriasis undergoing biologic therapy at a tertiary dermatology center in Southeastern Europe to evaluate potential correlations with SK development. Smokers had fewer SKs, whereas postmenopausal women and osteoporosis patients had significantly higher SK counts, implicating hormonal influences. PUVA therapy was linked to an increased SK count, whereas UVB and methotrexate treatments had a lesser effect. These findings suggest that biologic therapy and systemic factors may influence SK development, emphasizing the need for further prospective research.